Soil carbon policies in Ethiopia and Kenya: evolution, challenges, and opportunities - Omiti, John; Girvetz, Evan Hartunian; Andama, Mosoti; Nyawira, Sylvia (Bioversity International and the International Center for Tropical Agriculture, 2021)
The policy brief provides a general statues of the soil carbon policies in Kenya and Ethiopia